2020
DOI: 10.3389/fchem.2020.599893
|View full text |Cite
|
Sign up to set email alerts
|

Control and Transfer of Chirality Within Well-Defined Tripodal Supramolecular Cages

Abstract: The development of new strategies to turn achiral artificial hosts into highly desirable chiral receptors is a crucial challenge in order to advance the fields of asymmetric transformations and enantioselective sensing. Over the past few years, C 3 symmetrical cages have emerged as interesting class of supramolecular hosts that have been reported as efficient scaffolds for chirality dynamics (such as generation, control, and transfer). On this basis, this mini review, which summarizes the existing examples of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Moreover, the aromatic rings of the linkers adopt a helical arrangement: the chirality of the CTV propagates along the linkers and the lateral arms present a Λ (respectively Δ ) propeller-like arrangement that is imposed by the M configuration (respectively P ) of the CTV unit. 29 This induces a strong twist of the whole framework leading to extremely narrow windows and probably precluding the access of a basic molecule to the azaphosphatrane center. This could account for the lack of reaction between the acidic azaphosphatrane unit and the basic − CD 2 CN, MeO − , NaH or t -BuO − .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the aromatic rings of the linkers adopt a helical arrangement: the chirality of the CTV propagates along the linkers and the lateral arms present a Λ (respectively Δ ) propeller-like arrangement that is imposed by the M configuration (respectively P ) of the CTV unit. 29 This induces a strong twist of the whole framework leading to extremely narrow windows and probably precluding the access of a basic molecule to the azaphosphatrane center. This could account for the lack of reaction between the acidic azaphosphatrane unit and the basic − CD 2 CN, MeO − , NaH or t -BuO − .…”
Section: Resultsmentioning
confidence: 99%
“…In this context, C 3 symmetrical cages have emerged as an interesting class of supramolecular compounds for studying chirality dynamics [44]. Among others, this phenomenon was recently observed with the family of face-rotating polyhedral [45][46][47][48][49][50][51].…”
Section: Introductionmentioning
confidence: 97%
“…In particular, it was shown that the chirality of the cyclotriveratrylene unit (CTV), once included in a C 3 -symmetrical hemicryptophane cage, can propagate along the linkers to control the chirality of both the arms and the other unit located at the opposite side of the cage. 2 …”
Section: Introductionmentioning
confidence: 99%